Suitability research on the cavitation model and numerical simulation of the unsteady pulsed cavitation jet flow. Issue 1 (May 2016) - Chen, S Y; Yu, X F; Luan, D Y; Qu, Y P; Zhou, C
Abstract: In order to explore the cavitation jet mechanism, it can first study its critical state of single-phase flow before cavity occurrence to explore the trend of pulsed cavitation jet. Then select the cavitation model to simulate the complex multiphase flow state. Such a step-by-step approach is beneficial to advance research reliably and steady, relying on the foundation for further solving the problem. Three turbulence models such as Euler Hybrid Model, Euler Two Phase Model and Euler Lagrange Model are discussed on their suitability. In this paper, it states only RNG k- ε turbulent model can simulate small scale vortex of jet in the transient simulation. Grid independent verification and the effect of time step is presented. The simulation results show that a large scale vortex ring surrounding jet flow in the nozzle, the pressure of vortex core is slightly lower than the upstream nozzle pressure. Considering the capture ability of small scale eddies, an equivalent pressure is established. The single-phase flow turbulence model is modified to simulate the turbulence flow in the self-excited pulsed cavitation after the cavitation occurs. Through different results comparison of not modified cavitation model and the modified cavitation model to the experimental results, it proves that the latter simulation results are relatively accurate.